2004
DOI: 10.1063/1.1812831
|View full text |Cite
|
Sign up to set email alerts
|

Determination of energy barrier profiles for high-k dielectric materials utilizing bias-dependent internal photoemission

Abstract: We utilize bias-dependent internal photoemission spectroscopy to determine the metal/dielectric/ silicon energy barrier profiles for Au/ HfO 2 / Si and Au/ Al 2 O 3 / Si structures. The results indicate that the applied voltage plays a large role in determining the effective barrier height and we attribute much of the variation in this case to image potential barrier lowering in measurements of single layers. By measuring current at both positive and negative voltages, we are able to measure the band offsets f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…1͑b͒. Sample A was designed using thicknesses of 4 nm/3 nm/4 nm/3 nm/4 nm for Al 0.33 Ga 0.66 N/ Al 0.66 Ga 0.33 N/AlN/Al 0.66 Ga 0.33 N/Al 0.33 Ga 0.66 N layers in order to create a pseudomorphic structure whereby the layer thicknesses were in close proximity of the critical thickness values for an Al x Ga 1−x N / GaN heterostructure calculated by Floro et al 15 and Lee et al 16 The Al x Ga 1−x N / GaN heterostructure is expected to begin strain relaxation by generation of surface cracks, 12 which is not observed in either structure. The total thickness of the Al x Ga 1−x N barrier structure for the two devices was 18 nm ͑sample A͒ and 30 nm ͑sample B͒.…”
mentioning
confidence: 92%
“…1͑b͒. Sample A was designed using thicknesses of 4 nm/3 nm/4 nm/3 nm/4 nm for Al 0.33 Ga 0.66 N/ Al 0.66 Ga 0.33 N/AlN/Al 0.66 Ga 0.33 N/Al 0.33 Ga 0.66 N layers in order to create a pseudomorphic structure whereby the layer thicknesses were in close proximity of the critical thickness values for an Al x Ga 1−x N / GaN heterostructure calculated by Floro et al 15 and Lee et al 16 The Al x Ga 1−x N / GaN heterostructure is expected to begin strain relaxation by generation of surface cracks, 12 which is not observed in either structure. The total thickness of the Al x Ga 1−x N barrier structure for the two devices was 18 nm ͑sample A͒ and 30 nm ͑sample B͒.…”
mentioning
confidence: 92%
“…The resulting photocurrent is analyzed as a function of incident photon energy or as a function of applied bias to estimate the potential energy discontinuity at the heterointerfaces. 28 Au contacts of large size (1 mm diameter) were used as the top Schottky electrode for IPE measurements to ensure maximum collection of the incident radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows an IPE spectrum of the device taken under different applied bias voltages. Potential barrier at every bias is calculated by extrapolating the linear region of the (photocurrent) 1/3 versus incident wavelength plot as discussed by Brewer et al [8] and shown in the inset of Fig. 2.…”
Section: Experimental Conditionsmentioning
confidence: 99%